2009
DOI: 10.2174/156802609789909812
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Biological Explorations of the Family of CC-1065 and the Duocarmycin Natural Products

Abstract: CC-1065, the duocarmycins and yatakemycin are members of a family of ultrapotent antitumour antibiotics that have been the subject of extensive investigations due to their mode of action and potential in the design of new anticancer therapeutics. The natural products and their analogues exert their effects through a sequence selective alkylation of duplex DNA in the minor groove at the N3 of adenine. An understanding of their structure and its effect on biological activity has been derived through chemical syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 150 publications
(197 reference statements)
1
45
0
Order By: Relevance
“…In this study, we evaluated ICT2700, a chloromethylpyrroloindoline, which is rationalized to undergo CYP1A1-mediated oxidation resulting in production of an ultrapotent DNA alkylating cytotoxin. ICT2700 is a synthetic modification of the seco-duocarmycins as an approach to address the unmet clinical potential of this family of agents, which have failed to show an acceptable therapeutic index in clinical trials (17). We showed a significant increase in in vitro cytotoxicity of ICT2700 in RT112 (CYP1A1 positive) but not in EJ138 (undetectable CYP1A1) human bladder tumor cell lines.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…In this study, we evaluated ICT2700, a chloromethylpyrroloindoline, which is rationalized to undergo CYP1A1-mediated oxidation resulting in production of an ultrapotent DNA alkylating cytotoxin. ICT2700 is a synthetic modification of the seco-duocarmycins as an approach to address the unmet clinical potential of this family of agents, which have failed to show an acceptable therapeutic index in clinical trials (17). We showed a significant increase in in vitro cytotoxicity of ICT2700 in RT112 (CYP1A1 positive) but not in EJ138 (undetectable CYP1A1) human bladder tumor cell lines.…”
Section: Discussionmentioning
confidence: 84%
“…17). We showed previously that CYP1A1 oxidation restores the hydroxyl group critical to the spirocyclization mechanism necessary for DNA alkylation ( Fig.…”
Section: Differential Activation Of Ict2700 In Human Bladder Cancer Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Also promising for GDEPT are the nitro-chloromethylbenzindolines (nitro-CBIs), originally designed to be hypoxia-activated prodrugs [9] of amino analogues of the cyclopropylindoline anti-tumour antibiotics, exemplified by CC-1065 and duocarmycin SA [10,11]. It has been shown that the Escherichia coli nitroreductase NfsB (NfsB_Ec) can reduce nitro-CBIs in an oxygen-independent fashion, generating highly cytotoxic metabolites that alkylate the N3 of adenine in the minor groove of DNA [12].…”
Section: Introductionmentioning
confidence: 99%
“…Both, duocarmycins and yatakemycin may lead to the development of other natural products [18]; an extract of the fruit from Xylopia aethiopica demonstrated an antiproliferative action on human cervical cancer cells [19], while extracts of the leaves of Brysocarpus coccineus have suggested their potential use in cancer chemotherapy [20].…”
Section: Anticancer Drugsmentioning
confidence: 99%